Prior prescription opioid misuse in a cohort of heroin users in a treatment study. (December 2018) - Fendrich, Michael; Becker, Jessica
Abstract: This study investigates prior prescription opioid misuse in a cohort of heroin users whose progress was tracked in a treatment study conducted in the US from 2006 to 2010. Half of the sample misused prescription opioids ("other opiates/analgesics") prior to their onset of heroin misuse (POBs). We found that POBs were demographically younger and more likely to be white than other heroin users (OHUs). There were differences between the two groups with respect to the reporting of at least one year of regular use of substances and age of onset of substance use. POBs were more likely to report regular use, and earlier onset of use of several substances, mostly of the type potentially obtained via prescription. POBs were more persistent in their opioid use and more likely to suffer near-term elevated depressive symptoms compared with OHUs. These findings suggest that heroin addiction treatment may need to be tailored according to opioid misuse history. Highlights: A cohort of heroin users enrolled in a treatment study early in the current US heroin crisis was followed About half of the heroin users misused other opiates/analgesics before they misused heroin Those whose other opiates/analgesic misuse occurred before heroin misuse were younger and more likely to be white At follow-up, there were symptom and substance use differences between the groups At 12-month follow-up, those who transitioned to heroin from POs reported greater use of POs than other heroin users Treatment for heroin dependence may need to consider opioid use history